(untitled) (Bangladesh Journal of Animal Science, 2023)
Livestock plays a crucial part in the global food chain; however, its production and supply could be jeopardized due to climate change-related risks. Therefore, this study gathered information regarding adverse climatic livestock production, adaptation, and mitigation strategies to the hazards’ impact, finding research opportunities, and suggesting ideas for policymaking. The impact of increased temperature, altered rainfall, drought, flood, riverbank erosion, salinity, natural calamities like cyclones, etc. on livestock production was reviewed and reported in this article. They are responsible for reducing the availability and quality of fodder and water, declining livestock growth and reproduction, spreading diseases, and posing a threat to animal genetic resources. On the other hand, Bangladesh is anticipated to descend under water as a result of sea level rise resulting in a saline incursion into cropland and freshwater, drastically affecting crop and livestock production, especially in coastal regions. The impact of the hazards can be reduced through following some mitigation and adaptation strategies such as adopting and improving local breeds, practicing mixed farming systems, embracing climate smart livestock management systems, providing insurances for the losses to farmers, and so on. Feeding practices can be altered during flood by providing tree leaves, UMB, unconventional feeds. In conclusion, this review provided a compiled knowledge of climate change affecting livestock production, identifies the research gaps and suggests further research opportunities in this sector. Bangladesh Journal of Animal Science 52 (1): 1-14, March 2023